The use of Carboxytherapy alone or in combination with fractional CO2 laser for facial rejuvenation: A split‐face comparative study. (24th May 2020) - El‐Domyati, Moetaz; Hosam El‐Din, Wael; Medhat, Walid; Ibrahim, Michel R.; Khaled, Yasmin
Abstract: Background: A wide variety of minimally invasive treatments are available for skin aging. Recently, carbon dioxide therapy (CDT) or carboxytherapy was used in many cosmetic indications including facial rejuvenation. Objective: To compare the efficacy of CDT alone versus combined CDT and fractional CO2 laser in management of facial aging. Methods: Twenty‐Five female patients with bilateral and symmetrical facial aging were included in the study. The right (Rt) hemiface received 8 sessions of CDT whereas the left (Lt) side was treated with combined technique (6 sessions of CDT and 2 sessions of fractional CO2 in between. Clinical and objective evaluation using 3D skin analysis, histological, and morphometric analysis were performed. Results: Clinical evaluation demonstrated that all patients (100%) were satisfied with no significant difference between both sides of the face ( P > .05). Regarding texture and pigmentation improvement, the Lt side (combined) showed significant improvement compared to the Rt side ( P < .05). Using Antera 3D camera, there was a significant difference ( P < .05) in 3D improvement percent in textural changes while there was no significant difference ( P > .05) in the 3D percent of wrinkles improvement between both sides. The Lt side showed more significant increase in epidermal thickness after treatment when compared to the Rt side ( P < .05) with evident neocollagen formation. Conclusion: Carboxytherapy is an easy, safe, simple, and a relatively effective method for facial rejuvenation with minimal downtime. Better results were achieved when used in combination with fractional CO2 laser.